2006
DOI: 10.1177/154193120605001622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensory Modality on Vigilance Performance and Cerebral Hemovelocity

Abstract: Using Transcranial Doppler sonography, cerebral blood flow velocity (hemovelocity, CBFV) was recorded from the middle cerebral arteries during the performance of 40-min auditory and visual vigilance tasks. Reductions in stimulus duration were the critical signals for detection in both tasks, which were equated for stimulus salience and discrimination difficulty. Signal detection responses (correct detections and false alarms) and CBFV declined linearly over time in both modalities. In addition, the overall lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, several studies have reported that correlations between the two modalities are either low (r < .30) or nonsignificant (Warm & Jerison, 1984). Accordingly, in a recent study (Shaw et al, 2006) we sought to determine the degree to which the vigilance decrement is accompanied by a decline in cerebral blood flow velocity in comparable visual and auditory vigilance tasks.…”
Section: The Sensory Factor Studymentioning
confidence: 99%
“…In addition, several studies have reported that correlations between the two modalities are either low (r < .30) or nonsignificant (Warm & Jerison, 1984). Accordingly, in a recent study (Shaw et al, 2006) we sought to determine the degree to which the vigilance decrement is accompanied by a decline in cerebral blood flow velocity in comparable visual and auditory vigilance tasks.…”
Section: The Sensory Factor Studymentioning
confidence: 99%
“…This was the case regardless of the initial reference cue intensity. One proposed explanation for this finding would be the longer duration of tactile (haptic) sensory memory (~ 5-10 seconds), compared to visual (iconic, ~300-500 milliseconds), and auditory (echoic, ~3-4 seconds) memory (Colheart, 1980;Gilson & Baddeley, 1969;Sperling, 1960). As a result, participants may have replayed the tactile reference stimuli less often than the visual and auditory ones, and instead relied more on memory than actual perception and relative judgments.…”
Section: Discussionmentioning
confidence: 96%
“…Brill et al, 2007Brill et al, 2008Brill et al, 2009Garcia et al, 2009Scerra & Brill, 2012Shaw, 2006Terrence et al, 2005 Tables 1 and 2 highlight the lack of an agreed-upon crossmodal matching technique and raise questions about the validity and reliability of the various approaches. For example, given the potential for large intra-individual variability of crossmodal matches (Teghtsoonian & Teghtsoonian, 1983), it may not be sufficient to obtain a single match value from a participant for any given modality pair.…”
Section: Introductionmentioning
confidence: 94%